MÉTODO DOCUMENTÁRIO E A ANÁLISE DAS ORIENTAÇÕES GERACIONAIS DA JUVENTUDE - Tavares, Breitner Luiz (Caderno CRH, 2013)
Considerando a diversidade teórico-metodológica dos estudos sobre juventude no Brasil e no exterior, este trabalho faz uma apresentação geral da contribuição teórica do método documentário desenvolvido a partir de Karl Mannheim para a pesquisa qualitativa em Ciências Sociais. Dessa forma, observa-se o potencial analítico do método para o estudo das orientações coletivas promovidas pela juventude, no sentido da construção de um estilo de vida em torno da cultura jovem, como fator preponderante para a configuração geracional. Em termos empíricos, este artigo propõe a abordagem do problema referente à marginalização da juventude de comunidades localizadas na periferia urbana do Distrito Federal, tendo por referência Ceilândia. Mais precisamente, o recorte analítico é o estilo de vida em torno da cultura hip-hop praticada por jovens no Distrito Federal, compreendido como mecanismo produtor de suas orientações coletivas. PALAVRAS-CHAVE: Método documentário. Orientações coletivas. Juventude. Hip hop. Distrito Federal. DOCUMENTARY METHOD AND THE ANALYSIS OF GENERATIONAL ORIENTATION S OF YOUTH Breitner Luiz Tavares Considering the theoretical-methodological diversity of studies about youths inside and outside Brazil, this paper provides a general presentation of the theoretical contribution of the documentary method developed since Karl Mannheim for qualitative research on Social Sciences. Thus we may observe the analytical potential of the method for studying the collective orientations encouraged by young people in order to establish a life style centered on youth culture as a preponderant factor for generational configuration. In empirical terms, this article proposes an approach to the problem with regard to the marginalization of young people in communities located in the outskirts of the Federal District, taking Ceilândia as an example. More precisely, the analytical cross-section is the life style of the hip-hop culture embraced by the youth of the Federal District, which is understood to be a mechanism for producing their collective orientations. KEY WORDS: Documentary method. Collective orientations. Youth. Hip hop. Federal District. LA MÉTHODE DOCUMENTAIRE ET L’ANALYSE DES ORIENTATIONS GÉNÉRATIONNELLES DE LA JEUNESSE Breitner Luiz Tavares Compte-tenu de la diversité théorique et méthodologique des études sur les jeunes au Brésil et à l’étranger, ce travail donne un aperçu de la contribution théorique de la méthode documentaire développée à partir de Karl Mannheim en matière de recherche qualitative en Sciences Sociales. Ainsi, il est possible d’observer le potentiel analytique de la méthode pour l’étude des orientations collectives promues par les jeunes, dans le sens de la construction d’un mode de vie d’une culture jeune, comme facteur prépondérant pour la configuration d’une génération. En termes empiriques, cet article propose une approche du problème concernant la marginalisation des jeunes des communautés situées dans les banlieues urbaines du District Fédéral, avec pour référence la région de Ceilândia. Plus précisément, l’échantillonnage destiné à l’analyse est celui du vécu de la culture hip-hop des jeunes du District Fédéral, considérée comme un mécanisme de production de leurs orientations collectives. MOTS-CLÉS: Méthode documentaire. Orientations collectives. Jeunesse. Hip hop. District Fédéral. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;"> Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; display: inline ! important; float: none;"> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br